2018
DOI: 10.1088/1361-6455/aac8fa
|View full text |Cite
|
Sign up to set email alerts
|

Vibrationally resolved electron-impact excitation cross sections for singlet states of molecular hydrogen

Abstract: electronic states of molecular hydrogen. Here we apply the adiabatic nuclei convergent close-coupling method formulated in two-center prolate spheroidal coordinates. We find significant disagreement with previous calculations, where available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…The satisfactory agreement found tells about the agreement of vibronic excitations to excited singlet states, and the same general considerations can be extended to dissociative excitation processes induced by electron impact (a thorough comparison can be found in Refs. [29,30]), thus confirming that the semi-classical approach could be a reasonable choice for non-resonant excitations in dipole-allowed transitions. In fact, also the H 2 dissociation by electron impact is of great importance in any vibrational kinetic scheme, being the process responsible for destroying the vibrational content of molecules on the one hand and possibly leading to the production of excited atomic species on the other.…”
Section: Global Models and Relevant Elementary Processes In Caesium-free Nis: Early Studiessupporting
confidence: 52%
See 1 more Smart Citation
“…The satisfactory agreement found tells about the agreement of vibronic excitations to excited singlet states, and the same general considerations can be extended to dissociative excitation processes induced by electron impact (a thorough comparison can be found in Refs. [29,30]), thus confirming that the semi-classical approach could be a reasonable choice for non-resonant excitations in dipole-allowed transitions. In fact, also the H 2 dissociation by electron impact is of great importance in any vibrational kinetic scheme, being the process responsible for destroying the vibrational content of molecules on the one hand and possibly leading to the production of excited atomic species on the other.…”
Section: Global Models and Relevant Elementary Processes In Caesium-free Nis: Early Studiessupporting
confidence: 52%
“…2. Density of atomic H 0 in the gap between PG and EG (29). It is related to the molecule dissociation degree which in turn affects the mass flow outside the ion source and inside the accelerator.…”
Section: Application To Nio1mentioning
confidence: 99%
“…dissociative ionization via B 1 Σ + u , C 1 Π u , B ′1 Σ + u ). Dissociation via B ′1 Σ + u singlet state appears one of the dominant channel producing low energy atoms, for the high temperature case (cross section peaks near threshold [35], but this is not the case of recent results [51]). Dissociation via a 3 Σ + g and c 3 Π u are the main contribution for fragments at around 1 eV: their contribution reaches low energies all the way to ∼0 eV, due to the mixing of the vibrational levels towards higher 𝑣.…”
Section: Contribution From Individual Collisional Processesmentioning
confidence: 83%
“…Secondly, the IP method uses classical trajectories to model the scattering electron. This description is not accurate until much higher energies, as noted by Tapley et al (2018) who found that the IP results significantly overestimated the cross sections for dipole-allowed states below scattering energies of 100 eV. Thirdly, we have performed a fixed-nuclei calculation which is being compared to a vibrationally resolved cross-section.…”
Section: Resultsmentioning
confidence: 99%